Decreased Motivation as a Reason for Switching Normal Labor from Obstetricians to Midwives in Hospitals - Kusuma Wardhana, Eka Chandra; Nuthea, Merry; Hariyanti, Tita (Jurnal Kedokteran Brawijaya, 2022)
Based on the regulations, normal delivery with complications referred to a mother and child hospital is not under the right and obligation of the midwife as a maternity leader but must be led by an obstetrician. However, 58% of the normal deliveries were referred to midwives at Puri Bunda Mother and Child Hospital. This study aimed to explore the cause of the transfer of leadership in normal deliveries from obstetricians to midwives as the basis for developing solutions to the problems. This research was qualitative with a case study approach. Data were collected through focus group discussions, unstructured observations, and in-depth interviews. The total number of participants involved in this study was 16 people. Focus group discussions were conducted with midwives in the delivery room. In-depth interviews were conducted with the hospital director, the head of the delivery room, and obstetricians who provide normal delivery services. The results showed no guidelines and policies regarding the transfer of normal deliveries.